Розробка компонентів інформаційно-облікової системи продажу картин - Янополь, І. В. (ХНУРЕ, 2024)
The primary aim of developing components for an information and accounting system for selling paintings is to streamline and optimize the entire process of managing and selling artworks. Creating a reliable online platform to facilitate the sale of paintings will enable the expansion of the art market. Simultaneously, it will serve as a convenient and effective way for art enthusiasts to start or add to their collections of paintings. This system should feature a scalable architecture to support the ongoing development of the service. Additionally, the scalable architecture will ensure that the information and accounting system can adapt and grow alongside the increasing demands and evolving requirements of both the art market and users' needs.
Keywords: інтерфейс користувача; база даних картин; система оформлення замовлень; управління запасами; облік платежів